PENELITIAN TINDAKAN KELAS DALAM PEMBELAJARAN STRATEGI PEMBELAJARAN PADA MAHASISWA SEMESTER III DI PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP UM TAPSEL - Dewi, Shoufi Nisma (CV. Alfa Pustaka, 2024)
This research aims to improve the understanding and skills of students in the third semester of the FKIP UM Tapsel English Education Study Program in choosing and implementing effective learning strategies. Using the Classroom Action Research (PTK) method, this research was conducted in three cycles, with each cycle focusing on different learning strategies, such as cooperative, problem-based, and project-based learning. The subjects of the study were 30 students enrolled in the English language learning strategy course. The results of the study show that in the first cycle, students understand the basic theory of learning strategies, but have difficulty connecting them with practice. In the second cycle, 70% of students successfully implemented problem-based strategies, and 60% were able to manage classes effectively. In the third cycle, the use of project-based learning improved the skills of 85% of students in designing and implementing